A comprehensive cartographic approach to evacuation map creation for Hurricane Ike in Galveston County, Texas. Issue 1 (1st January 2016) - Chen, Yin-Hsuen; Zick, Stephanie E.; Benjamin, Adam R.
Abstract: Hurricane evacuation maps raise awareness of the risks associated with potential inundation from storm surge and provide evacuation route information to residents leaving their residences for safety. To create the most effective hurricane evacuation map for communicating risk to the public, cartographic best practices must be integrated into the evacuation map visualization. This study addresses a current gap in the scientific literature by integrating cartographic best practices for color choice, symbol choice, and positive messaging, together with a complete GIS-based workflow utilizing LiDAR-derived digital elevation models, Sea, Lake and Overland Surges from Hurricanes (SLOSH) storm surge products, and vector shapefiles for creating hurricane evacuation maps. To evaluate the methodology, the primary study site was Galveston County, Texas, during Hurricane Ike in September 2008. The typical workflow for county and municipal emergency managers is to create pre-hurricane season generalized evacuation maps. This study shows that the probabilistic storm surge SLOSH forecasts can be seamlessly implemented in the 72–48 hours prior to a storm surge event to provide specialized evacuation maps that incorporate hurricane-specific parameters and more accurately show risk to residents. To verify the Hurricane Ike workflow, a secondary study site in Harrison County, Mississippi, was used to evaluate Hurricane Isaac in August 2012. This study provides a comprehensive cartographic methodology for evacuation zone mapping when the US coastline is threatened by a landfalling hurricane.